The Organizational Climate and their effect on Organizational loyalty among Kindergartens Teachers in Lattakia city - Afield Study - Ali, Wafegah (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research aimed to recognize the reality of the prevailing organizational climate in of kindergartens institutions, and recognize the degree of organizational loyalty among kindergartens teachers, also recognize the impact of organizational climate on organizational loyalty among kindergartens teachers in Lattakia city, also the impact of the variables (the authorities supervising, the training courses, years of experience, the scientific qualification) in organizational climate and in organizational loyalty among kindergartens teachers. To achieve the object of the research a questionnaire has been included two dimensions to measures the organizational climate and organizational loyalty then applied to a sample of (174) kindergarten teachers for the academic year 2019/2020, and used the descriptive analytical method. validity of the questionnaire was established though a jury of (7) of the teaching staff of educational at Damascus and Tishreen universities. pilot sample consisted of (28) kindergarten teachers, reliability was established by Cronbach – alpha reliability (0.889) for organizational climate, and (0.902) for organizational loyalty, which indicate to high reliability to questionnaire. The research results showed that the organizational climate of kindergartens institutions came within a middle –grade, and the degree of organizational loyalty among kindergartens teachers came within a high-grade, also there are found the a correlation connection between the organizational climate and organizational loyalty among kindergartens teachers. In fact there are found Impact of the variables (the authorities supervising, the training courses, years of experience, the scientific qualification) in organizational loyalty, and haven’t shown the impact of these variables in organizational climate of kindergartens teachers in Lattakia city. هدف البحث الحالي تعرف واقع المناخ التنظيمي السائد في مؤسسات رياض أطفال، وتعرف درجة الولاء التنظيمي لمعلمات رياض الأطفال في مدينة اللاذقية، وتعرف أثر المناخ التنظيمي في مستوى الولاء التنظيمي لمعلمات رياض الأطفال في مدينة اللاذقية، وكذلك تعرف إلى أثر المتغيرات الآتية: (تابعية الروضة، الدورات التدريبية، عدد سنوات الخبرة، المؤهل العلمي والتربوي) في المناخ التنظيمي، وفي الولاء التنظيمي لمعلمات رياض الأطفال. ولتحقيق هدف البحث صممت استبانة مؤلفة من بعدين لقياس درجة وجود واقع المناخ التنظيمي السائد في رياض أطفال الولاء التنظيمي لمعلمات رياض الأطفال، وطبقت على عينة مؤلفة من (174) معلمة روضة للعام الدراسي 2019/2020، واستخدم المنهج الوصفي، وتم التحقق من صدقها بعرضها على (7) محكمين مختصين في جامعتي دمشق وتشرين، وتم التحقق من ثباتها بتطبيقها على عينة استطلاعية بلغت (28) معلمة روضة، من خلال معامل ألفا كرونباخ (Cronbach – Alpha)، الذي بلغ (0.889) لبُعد واقع المناخ التنظيمي السائد في رياض أطفال، (0.902) الولاء التنظيمي لمعلمات رياض الأطفال، وهذا يشير إلى ثبات عالٍ للاستبانة. بينت نتائج البحث أن واقع المناخ التنظيمي السائد في رياض أطفال جاء بدرجة متوسطة، وأن الولاء التنظيمي لمعلمات رياض الأطفال في مدينة اللاذقية جاء بدرجة مرتفعة، كما وجدت علاقة ارتباطية جيدة بين المناخ التنظيمي والولاء التنظيمي لمعلمات رياض الأطفال. ووجود أثر لتفاعل المتغيرات المستقلة (تابعية الروضة، الدورات التدريبية، عدد سنوات الخبرة، المؤهل العلمي والتربوي) الولاء التنظيمي لمعلمات رياض الأطفال في مدينة اللاذقية، وعدم وجود أثر لتفاعل هذه المتغيرات على المناخ التنظيمي السائد في رياض أطفال،